Asian Pacific Association of Gastroenterology (APAGE) Clinical Practice Guidelines on the Use of Small Molecules and IL-23 p19 Inhibitors in Ulcerative Colitis and Crohn's Disease - Ooi, Choon Jin; Ling, Khoon Lin; Limsrivilai, Julajak; Wei, Shu Chen; Mak, Joyce Wing Yan; Kobayashi, Taku; Dang, Luan Minh; Leong, Rupert W.; Lin, Huiyu; Weng, Meng Tzu; Ong, Wan Chee; Ahuja, Vineet; et al. (My University, 2026)
Ulcerative colitis (UC) and Crohn's disease (CD) are increasingly prevalent in the Asia Pacific region, necessitating updated, region-specific guidance on advanced therapies. Targeted small molecule agents, such as filgotinib, tofacitinib, upadacitinib, etrasimod, and ozanimod; and the IL-23 p19 inhibitors (guselkumab, mirikizumab, risankizumab) are the newest advanced therapies in our armamentarium for the treatment of IBD. The aim of the Asia-Pacific consensus statements is to provide context-specific recommendations integrating real-world evidence specific to our region. The Asian-Pacific Association of Gastroenterology (APAGE) Committee on Inflammatory Bowel Disease, with the participation of Asian Education Network in Inflammatory Bowel Disease (AEN-IBD), convened a forum of 34 IBD experts from 12 countries to develop consensus guidelines on the best practices on the use of these new advanced therapies using the modified Delphi method. IL-23 p19 inhibitors have shown good efficacy in biologic-naïve and experienced patients in both UC and CD, with clinical and endoscopic superiority over ustekinumab and an excellent safety profile. JAK inhibitors (tofacitinib and filgotinib) are efficacious in UC, and upadacitinib is efficacious in both UC and CD. They have a rapid time to response, and emerging data on acute severe UC appears promising. However, careful screening and monitoring is needed for known side effects, and prophylactic vaccination for herpes zoster should be considered. S1P modulators (ozanimod, etrasimod) are efficacious in UC with a favorable side effect profile.
Keywords: Asia; Crohn's disease; IL-23 p19 inhibitors; small molecules; UC